Study of Efficiency of Web Search Engine - Bharat Bhushan Kumar; Dr. A. R. Tripathy (International Journal of Scientific Research in Science and Technology, 2024)
In this paper, we consider caching which is a very effective technique to make scalable a service that distributes data to a multitude of clients. As suggested by many researchers, caching can also be used to improve the efficiency of a Web Search Engine (WSE). This is motivated by the high locality present in the stream of queries processed by a WSE, and by the relatively infrequent updates of WSE indexes that allow us to think of them as mostly read-only data.